Propuesta de un sistema de costos para la empresa tipografía y litografía arte clásico SAS de la ciudad de Cali. (2022)
This investigation is oriented in a PROPOSAL OF A SYSTEM OF COSTS BY PRODUCTION ORDERS FOR THE COMPANY LITOGRAFIA Y TIPOGRAFIA ARTE CLASICO SAS Calle 18 No. 575 Barrio San Nicolás identified with NIT 900.726.350 with address at Cali, Valle del Cauca.